Occurrence and distribution of cancers with emphasis upon oral cancers in registered oncology institutes of South India - A retrospective study - P K Asmin; Fareed Nusrath; Darshan D Divakar (Wolters Kluwer Medknow Publications, 2024)
Background: In the past two decades, the growing economy associated with changes in lifestyle-related behavior is partially responsible for the increasing cancer burden in India. To assess the occurrence and distribution of oral cancer based on the analysis of hospital records from registered oncology institutes of South India over a period of three years. Materials and Methods: A multicenter, retrospective study was conducted at seven major hospitals in South India to assess the incidence and distribution of cancer among patients over a period of three years (2016-2018). Data were collected on a custom-made validated proforma. Analysis was done using R commander software. Results: A total of 156090 various types of cancers were reported to the included institutes over a three-year period, an almost similar gender distribution was observed, males (n = 78806, 42.99% per lakh) compared to their female counterparts (n = 77284, 42.16% per lakh). Among males' lung cancer was the most common type with 17709 cases (9.65% per lakh) and among females, breast cancer was the leading cancer type with 22855 total cases (12.46% per lakh). Over a period of three years, a total of 21084 records of malignancies pertaining to oral cavity were identified accounting for 13.51% of cases. Among oral cancers, tongue was the most common site to be involved accounting for 44.22% (2016-2018) cases followed by buccal mucosa (14.69%), least common site to be involved was lip which accounted for 3.49% of the total oral cancer cases. Conclusion: Breast cancer was the most common cancer followed by lung cancer. Oral cancers occupied second among males and fifth rank in the order of occurrence among females. Tongue was the most common site followed by buccal mucosa. The least common site affected by oral cancer was the lip.